Business unit approach to managing commercial bank expenses ("Journal "U". Economy. Management. Finance.", 2024)
The article analyzes the business unit approach to managing the expenses of a commercial bank. It is determined that managing the operating expenses of a bank allows banking institutions to reduce expenses, increase competitiveness in the market, and improve profit indicators and business efficiency. One of such solutions is the implementation of the business unit approach to managing expenses in commercial banks. The business unit approach is a methodology where the emphasis is on decentralizing management and creating so-called business units. The implementation of this approach can also contribute to the development of an innovative culture in the bank, where each business unit will consider new ways to optimize expenses and improve efficiency. Such development may include automation of processes, implementation of new technologies and development of analytical competencies of employees. In the long term, the business unit approach can become an important element of the bank's competitive advantage, providing flexibility and adaptability in a rapidly changing financial environment. The author concludes that this problem has been little studied and requires further research.
Keywords: banking sector; business units; bank operating costs; financial and insurance activities; business unit; expenses